Answer:
The nth term of the given sequence is [tex]a_n = 54 \times (\frac{1}{3} )^{(n-1)}[/tex].
Step-by-step explanation:
Here, the first term of the sequence = 54
Second term = 18
Third term = 6
Now, [tex]\frac{18}{56 } =\frac{1}{3} [/tex]
and, [tex]\frac{6}{18 } = \frac{1}{3} [/tex]
as [tex]\frac{a_2}{a_1} = \frac{a_3}{a_2} =\frac{1}{3} [/tex]
Hence, the terms of the given sequence are in GEOMETRIC PROGRESSION with common ratio = 1/3
Now, the nth term in GP is given as [tex]a_n = a r^{(n-1)}[/tex]
So here, [tex]a_n = 54 \times (\frac{1}{3} )^{(n-1)}[/tex]
Hence, nth term of the given sequence is [tex]a_n = 54 \times (\frac{1}{3} )^{(n-1)}[/tex].